Dialectics of Regional Head Election Policy - Murtir Jeddawi; Riani Bakri; Arnas (Jurnal Pallangga Praja (JPP), 2026)
Regional head elections are essentially a form of public policy and, as such, represent a choice among various policy alternatives. The policy on regional head elections, as regulated in the laws concerning regional government and regional head elections, has been implemented through two models: elections conducted by regional legislative representatives (DPRD) and direct elections by the people. Both indirect and direct regional head elections involve the people as the holders of sovereignty. As a public policy, the mechanism of regional head elections continuously evolves in line with prevailing paradigms and the demands of the times. This paper focuses on examining the practice of regional head election policies in Indonesia, particularly the implementation of elections through the DPRD and direct elections by the people.